Nurses’ knowledge, attitude and practices on use of restraints at State Mental health care setting: An impact of in-service education programme - Rentala, Sreevani; Govinder Thimmajja, Sunanda; Bevoor, Prashant; Bevinahalli Nanjegowda, Raveesh (Investigación y Educación en Enfermería, 2021)
Objective. To evaluate the effectiveness of short-term in-service education program in improving nurse’s knowledge, attitude and self-reported practices related to physical restraint use. Methods. A quasi-experimental one group pre-post study was conducted involving nurses working at a tertiary mental health care setting, Dharwad, India. We provided 3 consecutive days of intensive restraint management education (total 6 hours-two hours per day) with a follow-up assessment after one month. The standard questionnaires on knowledge, attitude and practice regarding physical restraints were used as tools for measuring the impact of in-service education program. The program was conducted for a group of five to six nurses at a time. Teaching was done using lecture method, group discussion and demonstrations. Results. Of the 52 nurses who participated in the study, 52% were male, 58.5% had a baccalaureate degree. The mean age of respondents was 33.3 years, the mean work experience was 6.7 years. The findings of the study revealed that the mean scores on the knowledge regarding physical restraints increased after the in-service education from 6.4 to 8.2 (p<0.001). The mean attitude scores improved from 18.5 to 23.1 (p<0.001). There was a significant difference in mean practice scores between pre and post-intervention phases (23.7 versus 25.4; p<0.001). There was a significant correlation between post-test knowledge, attitude and practice scores. Conclusion. The in-service education program improved nurse’s knowledge, attitude and self-reported practice scores. This may lead to more effective restraints management by psychiatric nurses.